Biodegradation of recalcitrant chicken feather wastes by locally isolated heavy metal tolerant Alcaligenes sp. strain AQ05-001 - Yusuf, Ibrahim (2016)
The global increase in consumption of chicken meats as source of protein and the current use of chicken feathers as source of cheaply available biosorbent materials has led to the generation of large volume of recalcitrant melanised and non-melanised keratin containing primary and secondary feathers wastes in our environments. A need for eco-friendly method of managing these wastes became highly necessary.A novel bacterium isolated from feather dump site located in Johor, Malaysia identified by physical, biochemical and 16S RNA sequencing techniques as Alcaligenes sp. AQ05-001 was successfully used to degrade such feather wastes to produce keratinase enzyme and protein rich hydrolysates. Initially it only degraded 1 g/L of heavy metal polluted and un polluted feather wastes, produced 8.84 U/mL keratinase in 3 days. But upon optimisation of physical and nutritional factors using one-factor-at-a-time and response surface methodology approaches, complete degradation of almost 5 g/L feather and a 10-fold increase in keratinase production (88.0±1 U/mL) was recorded. The bacterium was immobilised in gellan gum gelling agent with its conditions optimised. With 0.8% gellan gum concentration, 3 mm size beads and 250 initial cell loads, immobilised cells degraded feathers at a faster rate and produced higher keratinase activities in optimised media. Both free and immobilised cells efficiently degraded recalcitrant melanised feathers faster than non-melanised feathers. They both showed a high preference for black feathers and complete degradation of 5 g/L of black feathers to dust and fibres was achieved in 18 and 24 h with immobilised and free cells, respectively. Interestingly, the strain further selectively degraded black feather completely in a flask containing 5 g/L mixture of equal amount of black, brown and white feathers, with leftover of brown feathers rachises at the end of 36 h incubation. Further, free and immobilised bacteria degraded large amount of feathers in optimised media. About 50 g/L feathers were degraded by immobilised cells while free cells degraded up to 40 g/L in 60 h with production of high amount of soluble protein hydrolysates that are rich in both essential and non-essential amino acids such as leucine, isoleucine, cysteine, aspartic acid and proline. Optimal adsorption of heavy metals by chicken feathers was carried out in broths within the pH range of 7-8.5 and temperature between 25-35°C. Both free and immobilised cells degraded feather-laden with single or combination of heavy metals with concurrent production of higher keratinase enzyme at varying rates. Beads were reused in biodegradation of feathers polluted with different heavy metals in semi-continuous fermentation for a number of cycles ranging from 4-10. Encapsulated cells tolerated up to 30 ppm of Ag, 20 ppm of Co, 15 ppm of Cu, 10 ppm of As, Ni, Cd and 5 ppm of Hg, Pb while free-living cells tolerated only 1 ppm of Hg and Pb. Moreover, cells in gellan gum degraded about 95% and above of feathers polluted with a mixture of 5 ppm each of Ag, As, Cd, Co, Cu, 10 and 20 ppm each of Ag, Co and Cu at 18 h. Beads that failed to degrade feathers laden with higher concentration of heavy metals like mercury, were used to degrade feathers laden with other heavy metals for many cycles without need for mineral acid desorption. Crude keratinase produced by strain AQ05-001 displayed relative activity over a temperature ranging from 30-60°C, pH 7-10 and was highly inhibited by serine inhibitor, Tween20, Trixton-100 and sodium dodecyl sulphate. However, cell-free crude keratinase was not able to degrade feathers efficiently, but improved degradation was observed in the presence of reducing agent (2 mercaptoethanol).The strain possesses the potential of being used in the management of melanised, non-melanised, heavy metal free/polluted feather as well as in the production of protein-rich hydrolysates for animal feeds and also in the industrial production of valuable keratinase enzyme. Furthermore, not only its heavy metals tolerability can be harnessed in the bioremediation of heavy metal-contaminated feather wastes, but it could also use the contaminated wastes as a substrate for keratinase production.